Gastric Microplastics in Clarias gariepinus of the Upper Vaal River, South Africa - Dahms, Heinrich T. J.; Tweddle, Gavin P.; Greenfield, Richard (Frontiers in Environmental Science, 2022)
Microplastics are defined as plastics smaller than 5 mm down to 0.05 mm. These plastics enter the environment and undergo certain physical changes, most notably density changes and a relative increase of surface size. Microplastics can then release or absorb toxicants from the surrounding environment. These plastics may then enter the food chain from producers to top predators. In this study, microplastics were investigated in four study sites in the upper Vaal River, South Africa. The goal of the study was to determine the levels of plastics in water, sediment and a top predator, the benthic fish Clarias gariepinus. In this study, a 10% KOH digestion of water and fish, and density separation of sediment with NaCl (1.2 g cm3) was used to extract microplastics for identification. Microplastics were detected in water (3, 300 particles m−³), fish (7.47 particles per fish) and sediment (46.7 particles kg−1). Microplastic intake was not attributed to the microplastic shape or size of the fish that ingested it. This highlights the need to understand how niche-specific microplastic concentrations are, which will not only aid in quantifying microplastics accurately in the environment but to better understand how they may influence various ecosystems.